2020
DOI: 10.3390/resources9110126
|View full text |Cite
|
Sign up to set email alerts
|

Success Factors for Water Safety Plan Implementation in Small Drinking Water Supplies in Low- and Middle-Income Countries

Abstract: Water Safety Plan (WSP) implementation has the potential to greatly improve, commonly very challenging and resource limited, small drinking water supplies. Although slower than in urban or high-income settings, the uptake of WSPs in low- and middle-income countries (LMICs) is accelerating. Understanding the factors which will make a WSP successful will further improve efficient uptake and assist with its long-term sustainability. Based on an extensive literature search using the Preferred Reporting Items for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…A study conducted by Herschan et al (2020) in Low-and Middle-Income Countries to identify the factors that contribute to a WSP's performance. The results showed that the most three essential success variables identified were technical capacity building, community engagement, and monitoring and verification.…”
Section: Water Safety Plans: the State Of The Art In Developing Count...mentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted by Herschan et al (2020) in Low-and Middle-Income Countries to identify the factors that contribute to a WSP's performance. The results showed that the most three essential success variables identified were technical capacity building, community engagement, and monitoring and verification.…”
Section: Water Safety Plans: the State Of The Art In Developing Count...mentioning
confidence: 99%
“…This variety is capable of accommodating disparities in the beliefs and worldviews of different stakeholders and, as a result, stimulates collaboration and understanding in environmental assessment procedures, promoting credibility and relevance. Clearly, the SEA tool recommends dedication, technical expertise, governance, and interagency collaboration (Herschan et al, 2020).…”
Section: Water Safety Plans: the State Of The Art In Developing Count...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although WSP implementation has been demonstrated to have led to improved drinking-water quality [13][14][15], the need for initial financial and technical resources have been identified [13,14,16]. Published studies of the direct outcomes and impacts of risk-based interventions are limited, especially for SDWS in SSA [12,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In order to make sure the safety of drinking water in Stockholm in 2001, a framework consisting of goals based on health, water safety plan and guidelines relative to the quality of drinking water was presented (9,10). Subsequently, the World Health Organization (WHO) introduced the Water Safety Plan (WSP) in 2004, which marked the largest change in global attitudes about how water resources are managed (11,12). One of the goals of the WSP is to manage the supply of safe drinking water from the source of production to the point of consumption (13).…”
Section: Introductionmentioning
confidence: 99%